2014
DOI: 10.1037/a0035724
|View full text |Cite
|
Sign up to set email alerts
|

Mental work demands, retirement, and longitudinal trajectories of cognitive functioning.

Abstract: Age-related changes in cognitive abilities are well-documented, and a very important indicator of health, functioning, and decline in later life. However, less is known about the course of cognitive functioning before and after retirement and specifically whether job characteristics during one's time of employment (i.e., higher vs. lower levels of mental work demands) moderate how cognition changes both before and after the transition to retirement. We used data from n = 4,182 (50% women) individuals in the He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
225
6
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(245 citation statements)
references
References 85 publications
(137 reference statements)
12
225
6
2
Order By: Relevance
“…6,8 In contrast, we focus on mid-adulthood, using a specific measure of occupation-related cognitive demands and complexity, providing evidence that higher levels of occupation-related cognitive requirements are not only associated with higher level of cognitive function, but also with a slower rate of decline. Our findings are consistent with another cohort study of American older adults, the Health and Retirement Study, which used a similar O*NET-derived measure of mental demands at work, 13 as well as a study of German older adults that used O*NET-derived measures of enriched work environment. 14 The exact mechanisms by which work-related cognitive demands and complexity may lead to slower cognitive decline later in life remain mostly unknown.…”
Section: )supporting
confidence: 80%
See 3 more Smart Citations
“…6,8 In contrast, we focus on mid-adulthood, using a specific measure of occupation-related cognitive demands and complexity, providing evidence that higher levels of occupation-related cognitive requirements are not only associated with higher level of cognitive function, but also with a slower rate of decline. Our findings are consistent with another cohort study of American older adults, the Health and Retirement Study, which used a similar O*NET-derived measure of mental demands at work, 13 as well as a study of German older adults that used O*NET-derived measures of enriched work environment. 14 The exact mechanisms by which work-related cognitive demands and complexity may lead to slower cognitive decline later in life remain mostly unknown.…”
Section: )supporting
confidence: 80%
“…Because of international differences in work environments and population heterogeneity, analysis in a US-based sample is important for generalizability to older Americans. Although findings similar to ours have been observed previously in a US-based cohort of older adults, 13 our findings are derived from a diverse cohort with a wide range of educational and occupational exposures, and using a well-validated, comprehensive assessment of cognitive function involving several tests administered in-person at regular intervals with high rates of follow-up participation.…”
Section: )contrasting
confidence: 34%
See 2 more Smart Citations
“…9 Occupational cognitive demands were also categorized using the O'NET SOC occupational codes. From these hierarchical taxonomic occupation-specific descriptors, Fisher et al observed that those with higher occupational demands experienced better cognitive functioning before retirement.…”
Section: Employment and Cognitive Reservementioning
confidence: 99%